Genetic Control of Ascorbic Acid Biosynthesis and Recycling in Horticultural Crops - Mellidou, Ifigeneia; Kanellis, Angelos K. (Frontiers in Chemistry, 2017)
Ascorbic acid (AsA) is an essential compound present in almost all living organisms that has important functions in several aspects of plant growth and development, hormone signaling, as well as stress defense networks. In recent years, the genetic regulation of AsA metabolic pathways has received much attention due to its beneficial role in human diet. Despite the great variability within species, genotypes, tissues and developmental stages, AsA accumulation is considered to be controlled by the fine orchestration of net biosynthesis, recycling, degradation/oxidation, and/or intercellular and intracellular transport. To date, several structural genes from the AsA metabolic pathways and transcription factors are considered to significantly affect AsA in plant tissues, either at the level of activity, transcription or translation via feedback inhibition. Yet, all the emerging studies support the notion that the steps proceeding through GDP-L-galactose phosphorylase and to a lesser extent through GDP-D-mannose-3,5-epimerase are control points in governing AsA pool size in several species. In this mini review, we discuss the current consensus of the genetic regulation of AsA biosynthesis and recycling, with a focus on horticultural crops. The aspects of AsA degradation and transport are not discussed herein. Novel insights of how this multifaceted trait is regulated are critical to prioritize candidate genes for follow-up studies toward improving the nutritional value of fruits and vegetables.